Navigating in the Digital Age: Uncovering Insights on Talent Management for Sustainable Performance - Bataineh, Mohammad Jamal; Aravamudhan, Varadaraj; Raj, M. Prasanna Mohan; Sengodan, Ananth (International Review of Management and Marketing, 2025)
Realizing that human capital is a critical factor in today’s strategic management, the study aims at analysing the possible ways through which organisations can improve organisational performance through talent management. This study examines the effects of talent management on sustainable organisational performance in corporate firms, India.. For this study the quantitative method was used, and the subjects were 218 managers and executives from different organisations using an online questionnaire. The study focuses on effective Talent Management practices that include talent acquisition, employee training, career progression, training and development, and employee turnover. Research findings show that policies such as remunerations, promotions, professional networking and flexible working hours are considered as antecedents of talent management. Additionally, the study establishes a strong positive correlation between talent management practices and organisational performance with reference to competitive advantages, morale and sustainability. A one-sample t-test and Pearson’s correlation test also provided strong support for the effect of talent management on short-term performance and long-term sustainable performance of the organisation. The article finds that 77% of participants agree that talent retention in their organization has led to an increase in sales. The study’s findings are important in the existing literature because there is limited research on talent management in emerging economies such as India. This paper therefore emphasizes the importance of the adoption of strategic talents management in organisations to guarantee organisational success in today’s more globalized economy. The research has relevance to practicing managers who seek to improve performance through the management of human capital.